MEDIA DAN REPRESENTASI IDENTITAS NASIONAL - Ika Puspa Dewi; Muhibbin (Al'Adalah, 2016)
National Identity as a characteristic which is possessed by the nation cannot be separated from the media to be used as information which is reported to the society. Through creativity, national identity has never finished in one place. Its presence criticize nationalist version while showing complexity and problematic of that national identity. In other words, national identity is not meant as artifact immutable, but it always get contestation politically and change continuously. This research is conducted to see how the construction of national identity of media, especially Jawa Post through Wayang Durangpo. Meanwhile, Wayang Durangpo is narrative which publishes weekly since 2009-2012. This research sees that media is not neutral. It means that media has the potential to be construction agent. This research used narrative analysis approach. Furthermore, the representation of national identity will be operated by using narrative codes, such as plot, intertextual, character, sintagmatig, paradigmatic, and binary opposition.